Biomarkers in Neurodegenerative Diseases 2.0 (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This book follows up on the previous volume focusing on the different biomarkers for neurodegenerative diseases. It includes original research works and review articles focusing on an improved understanding of disease mechanisms. It also aims to identify aspects of early therapeutic intervention for enhanced disease management. Some critical approaches include studies involving human tissue samples, mouse disease models, and different imaging techniques. These studies present the essential information necessary to address such pathological conditions in the future.